Biblical Hermeneutics and the Word about the Ineffable - René Dentz (Phainomena, 2023)
Paul Ricoeur’s engagement with biblical hermeneutics and his critique of Rudolf Bultmann’s existential hermeneutics shed light on the complex relationship between language, meaning, and religious experience. Following Ricoeur, it is necessary to distinguish two layers of understanding: the ideal layer of the text and the layer of signification, which is the moment when meaning is resumed for the reader and becomes effective in existence. The semantic moment must precede the objective and existential understanding, as well as action. Exegesis, therefore, involves two moments of understanding. If the text lacks objective meaning, it says nothing, and without existential appropriation, the Word is dead.